1973
DOI: 10.1021/ja00791a005
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates in the photochemistry of of carbonato-amine complexes of cobalt(III). Carbonate(-) radicals and the aquocarbonato complex

Abstract: The 254-nm irradiation of neutral, buffered, solutions of Co(NH3)4C03+ and Co(en)2C03+ produces Coaq2+ with a relatively low quantum yield (0.06 and 0.02, respectively); Co(NH3)6CQ3+ also is photoreduced. The irradiation of Co(NH3)4C03+ also generates Co(NH3)4(OH2)23+ with a quantum yield of 0.11 ± 0.03. The flash photolysis of the three complexes yields a transient intermediate which has 600 nm and which is identified as the C03~radical. The flash photolysis of the bidentate carbonato complexes also reveals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…Time-resolved, transient absorption experiments have shown that the photolysis of [Co(NH 3 ) 4 CO 3 ] + complexes induced by 248 nm KrF excimer, or 266 nm Nd: Yag laser pulses, yields CO 3 •− radicals. [19, 24, 25] Here we show that CO 3 •− radicals can also be produced easily by 308 nm XeCl excimer laser pulse excitation because the UV absorption spectrum of [Co(NH 3 ) 4 CO 3 ] + extends beyond 300 nm (i.e., beyond the absorption threshold of the normal DNA bases).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Time-resolved, transient absorption experiments have shown that the photolysis of [Co(NH 3 ) 4 CO 3 ] + complexes induced by 248 nm KrF excimer, or 266 nm Nd: Yag laser pulses, yields CO 3 •− radicals. [19, 24, 25] Here we show that CO 3 •− radicals can also be produced easily by 308 nm XeCl excimer laser pulse excitation because the UV absorption spectrum of [Co(NH 3 ) 4 CO 3 ] + extends beyond 300 nm (i.e., beyond the absorption threshold of the normal DNA bases).…”
Section: Resultsmentioning
confidence: 81%
“…[17] The conjugate acid (HCO 3 • ) is a strong acid (p K a < 0) and, at pH > 0, these radicals exist in the anion form, CO 3 •− . [29] The UV irradiation of [Co(NH 3 ) 4 CO 3 ] + complexes has been shown to generate different products according to two pathways : [19, 24, 25] …”
Section: Resultsmentioning
confidence: 99%
“…For many years, by analogy to the carbonate and bicarbonate anions, it was assumed that this radical normally exists as the protonated form (HCO 3 • ) in the neutral to basic pH range, but it is now firmly established that no protonation of CO 3 •− (reaction (10)) could be observed in the pH range of 0-10 [8], which leaves CO 3 •− as the only relevant carbonate radical species to be considered in this study and in most aquatic chemistry applications. This radical is a strong one-electron oxidant (1.78 [9] and 1.59 V [10] vs. Normal Hydrogen Electrode (NHE) at pH 7.0 and 12.5, respectively). Carbonate radical may be formed when using ultrasound for water treatment (quenching of hydroxyl radical by HCO 3 − and CO 3 2− ).…”
Section: Introductionmentioning
confidence: 99%
“…Carbonato tetrammine cobalt(III) perchlorate [Co(NH 3 ) 4 CO 3 ]ClO 4 was synthesized in two steps, as described elsewhere: (1) synthesis of [Co(NH 3 ) 4 CO 3 ]Cl [49] and (2) exchange of chloride anion with perchlorate anion [50]. …”
Section: Methodsmentioning
confidence: 99%
“…The carbonate radical anion (CO 3 •- ) was generated in situ by irradiation of the samples placed in quartz cuvettes with UV light [50; 51]. Photolysis was carried out using a 300 W Xe high pressure compact arc lamp (Eimac Model VIX 300 UV).…”
Section: Methodsmentioning
confidence: 99%